Projection of tsunami wave height at east-coast of Peninsular Malaysia using green's law - Aziz A.F.; Mardi N.H.; Malek M.A. (Science Publishing Corporation Inc, 2023)
In recent years, studies regarding a new source of tsunami-genic earthquake at South China Sea region known as Manila Trench earth-quake have attracted the attention of many researchers. It is expected that this subduction zone is capable to trigger large moment magnitude earthquake and affects countries located within South China Sea. The objective of this study is to project tsunami wave height and arrival time generated from Manila Trench earthquake towards coastal areas located along east-coast of Peninsular Malaysia. This study focuses on simulating tsunami at four different moment magnitudes by using TUNA-M2 model to record wave height and arrival time at the offshore areas. Then the Green's law is used to approximate reliable tsunami wave height when approaching onshore. Results obtained in this study showed that tsunami waves from Manila Trench are estimated to arrive at coastal areas of east-coast Peninsular Malaysia between 9.1 to 10.25 hours post-earthquake occurrence. The observation points located at offshore of Kelantan are anticipated to experience the highest wave height as compared to other observation points located at offshore areas of Terengganu and Pahang. This study is important to the coastal communities as it provides vital information on possible tsunami occurrences in the future. 2018 Authors.